Effects of team‐based learning about postpartum haemorrhage on learning outcomes and experience of midwifery students in Indonesia: A pilot study - Yunefit Ulfa; Yukari Igarashi; Kaori Takahata; Shigeko Horiuchi (Wiley, 2021)
Abstract Aim This pilot study aimed to evaluate the effects of team‐based learning about postpartum haemorrhage on the learning outcomes and experience of midwifery students in Indonesia. Design One‐group pre‐test-post‐test study. Methods This study enrolled 64 midwifery students as participants from an Indonesian health polytechnic school. This group attended two team‐based learning class sessions (90 min weekly for 2 weeks) on postpartum haemorrhage. Student learning outcomes and experience were assessed quantitatively. Results The mean knowledge score (0-100) was significantly higher at post‐test (mean = 85.9, SD 9.8) than at pre‐test (mean = 61.4, SD 12.9) (p < .001). There was a significant difference in the mean clinical reasoning score (12-60) between post‐test (mean = 35.4, SD 5.8) and pre‐test (mean = 21.3, SD 7.9) (p < .001). Most students (98.4%) engaged in classroom activities.